Strengthening the Role of Integrated Health Post Cadres in Child Protection Through Legal Psychology Education in Srigonco Village, Malang Regency - Masela, Minggus S.; Purborini, Vivi Sylvia; Prahoro, Alfedro Putut; Haq, Abdul; Maharani, Cantika Edenia (Civiliza Publishing, 2025)
This community service program aims to strengthen the role of Integrated Health Post (Posyandu ILP) cadres in child protection through legal psychology education in Srigonco Village, Malang Regency, Indonesia. Posyandu cadres serve as frontline community agents in monitoring child health and welfare; however, their understanding of children’s rights, legal protection, and psychological assistance for child abuse victims remains limited. This condition has contributed to the low level of early detection and reporting of child abuse cases at the village level. To address these challenges, this program implemented a series of educational interventions, including legal counseling on child protection laws, workshops on early detection and handling of child abuse cases, and training on psychological approaches for assisting child victims. The activities were conducted using participatory methods such as lectures, interactive discussions, case simulations, and role-playing. The effectiveness of the program was evaluated through pre-test and post-test assessments, observation, and participant feedback. The results indicate a significant improvement in cadres’ knowledge and skills regarding children’s rights, legal reporting mechanisms, and appropriate psychological assistance techniques. The cadres demonstrated increased confidence in identifying signs of abuse, providing initial support to victims, and coordinating with relevant authorities. Additionally, this program contributed to strengthening community awareness through educational campaigns involving local stakeholders. Overall, this community service initiative successfully enhanced the capacity of Posyandu cadres as agents of change in promoting child protection at the grassroots level. The program also reflects the synergy between academic institutions and local communities in creating a safer and more child-friendly social environment. The main output of this program is a scientific article targeted for publication in a nationally accredited journal.